A review on the synthesis of hydroxyapatite, its composites and adsorptive removal of pollutants from wastewater. (December 2020) - Pai, Shraddha; M Kini, Srinivas; Selvaraj, Raja; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Various synthesis methods of hydroxyapatite and its composites have been reviewed. Adsorptive removal of pollutants by HAP and its composites have been reviewed. Adsorptive removal mechanism of various pollutants has been outlined. Abstract: In the current study, the synthesis of hydroxyapatite (HAP) and its composite by various techniques, are abridged highlighting the eco-friendly technique – a green synthesis that involves the use of eco-friendly solvents like water and precursor substitution by waste resources. Magnetic HAP plays a major role in the HAP composites because of the ease of recovery and reuse. This study also emphasizes the prowess of the adsorption technique for the removal of various pollutants such as heavy metals, dyes, and emerging pollutants. A detailed adsorption mechanism is explained to understand the possible reactions taking place between the adsorbent and the adsorbate. Recent literature regarding the adsorption of various environmental pollutants by HAP and its composites are reported to support the efficiency of the adsorption process.